The implementation of electrochemical destruction process for decontamination of wastewaters of medical establishments - Самойленко, Наталья Николаевна; Ермакович, Ирина Анатольевна (Eastern-European Journal of Enterprise Technologies, 2014)
Studies, conducted at leading laboratories in Europe and the United States, have revealed that of microconcentrations of pharmaceutical preparations and their derivatives have a significant negative impact on the quality of surface and drinking water, natural food chains of biota, reproductive disorders, developmental abnormalities. Purification from pharmaceutical preparations (PP) at the existing treatment plants, carried out mainly by the biological method, is low for some of the most stable molecules. The content of such hardly-biodegradable substances can be reduced by applying additional aftertreatment methods, including using advanced processes, among which the electrochemical destruction. In Ukraine, the infected sewage of medical establishments before being discharged into the sewer system pass disinfection by chlorination. Given this fact, the authors have investigated the effect of the electrochemical destruction in the presence of chloride ions on the infected wastewater, contaminated with hardly-biodegradable PP (Diclofenac, Ibuprofen, β-estradiol). Criterion for evaluating the wastewater decontamination was the state of the enzymatic machinery of bacteria, namely their dehydrogenase activity, which is analyzed during the control of treated wastewater at municipal treatment plants. It was found that the infected solutions, containing Diclofenac, Ibuprofen and β-estradiol, before the electrochemical destruction cause only inhibitory effect on E. coli, which is somewhat higher than in the case of the presence of one PP (Diclofenac) in it. After the electrochemical destruction in the presence of chloride ions, solutions, containing three components when in contact with a suspension of E. coli have a pronounced bactericidal effect on it. It lies in inhibiting the enzymatic activity of bacteria, fixed by the instrumental method and determined by the absence of pharmazan in the studied solution. The results show the possibility of using the destruction of hardly-degradable medical products, as well as water decontamination from pathogenic microflora in a single electrochemical treatment process of infected wastewater of medical establishments, pharmaceutical preparations, containing pharmaceutical preparations.